FACIAL RECOGNITION WITH MACHINE LEARNING - JANS (NIM: 10114073), FRITZ
The development of the times and information and communication technology leads us to a surge of data. The work of processing extraordinary amount of data is very suitable given to the machine. But the ability of machine analysis is very low when compared with humans. We are interested to ﬁnd a way for the machine to learn the data provided by the user. We build artiﬁcial neural network structures that mimic the workings of human nerves. Then we ﬁnd a way to connect data with output. Using the optimization technique we create a backward propagation algorithm that can improve the relationship between values in artiﬁcial neural networks. The structure is then tested to work on simple problems ranging from solving equations, recognizing handwritten digit and ultimately capable of distinguishing the human face